Identification of qGL3.5, a Novel Locus Controlling Grain Length in Rice Through Bulked Segregant Analysis and Fine Mapping - Wang, Lan; Liu, Yang; Zhao, Haiyan; Zheng, Yuebin; Bai, Feng; Deng, Sicheng; Chen, Zhixiong; Wu, Jinwen; Liu, Xiangdong (Frontiers in Plant Science, 2022)
Grain length (GL) directly affects the yield and quality of rice. Very few cloned GL-related genes are applied in production because their yield-increasing effects are not obvious, and the overall regulatory networks underlying the associated processes remain poorly understood. DNA samples from two bulk DNA pools (L-pool and S-pool) and their parents (KJ01 and Huaye 3) were subjected to high-throughput sequencing. Using bulked segregant analysis (BSA), qGL3.5 was mapped to a 0.34-Mb “hotspot” region on chromosome 3 that contains 37 genes related to various traits. Then, qGL3.5 was mapped to the genomic interval between the flanking markers M2 and M3 using 2786 BC4F2 individuals. Because the region from B5 to B6 was not the associated region under BSA-seq analysis, qGL3.5 was narrowed down to the interval between B6 and M3, which spanned 24.0-kb. Of all 37 genes with nonsynonymous SNPs between KJ01 and Huaye 3 based on BSA-seq analysis, only one complete annotated gene, ORF18 (Gene ID: LOC_Os03g42790.1) was found. ORF18 encodes an IBR-RING zinc-finger-related protein, with one really interesting new gene (RING) and two in between ring fingers (IBR) domains. The knockout of ORF18 derived from Huaye 3 using CRISPR/Cas9 editing technology increased the GL of the mutant by approximately 2.2 mm. The novel locus qGL3.5 negatively regulated GL by promoting elongation of the longitudinal cell of the grain outer glume. These results provide a new genetic resource for rice grain shape breeding and a starting point for the functional characterization of the wild rice GL gene.